Is Multiple Gestation Associated with an Increased Risk of Placenta Previa ? : A Systematic Review - Carina Rhamadhanis; Yahya Nurlianto; Mutia Juliana (International Medical Journal Corp. Ltd, 2026)
Background: Placenta previa is a major cause of antepartum hemorrhage, preterm delivery, and maternal morbidity. Multiple gestation is frequently listed as a risk factor in clinical guidelines, yet direct comparative evidence remains sparse and inconsistent. This systematic review evaluates whether multiple gestation independently increases the risk of placenta previa after accounting for key confounders, particularly assisted reproductive technology (ART) and prior cesarean delivery. Methods: We systematically screened RCT, etc that compared multiple gestations (twins or higher-order) with singleton gestations and reported placenta previa as an outcome. Studies were required to provide sufficient data for calculating measures of association (OR, RR, or incidence proportions). Data extraction focused on study design, population characteristics, multiple gestation details, placenta previa definition, association results, confounder adjustment, and sample sizes. Only studies with statistically significant positive findings were emphasized for the primary analysis. Results: Among 80 identified studies, only four provided direct quantitative comparisons between multiple and singleton gestations for placenta previa. In a cohort of 14,583 cesarean deliveries (Guo et al., 2022), placenta previa incidence was significantly lower in multiple gestations (2.4%) than singletons (3.9%; p=0.012)—a counterintuitive finding. Among placenta accreta spectrum (PAS) cases, twins had significantly lower previa rates (38.1% vs. 71.9%; p<0.001) and fewer prior cesareans (median 0 vs. 2) (Shamshirsaz et al., 2020). ART-conceived dichorionic twins had a nearly threefold higher risk of placenta previa compared with naturally conceived twins (RR=2.99; 95% CI 1.51–5.92; p=0.002; I²=0%) (Qin et al., 2016). The ART-associated previa risk was significantly lower in twins (OR=1.50) than in singletons (OR=2.67) (Karami et al., 2018). After adjusting for multiple gestations, the crude ART–previa association attenuated from OR=4.6 to aOR=1.8 (Johnston et al., 2015). Discussion: The apparent clinical association between multiple gestation and placenta previa is largely explained by confounding. ART increases both twinning and previa risk, while prior cesarean—a dominant previa risk factor—is less common in multiples. The lower crude previa rate in multiples is explained by their lower burden of uterine scarring. Mechanistically, ART alters endometrial receptivity and trophoblast invasion independently of plurality. In PAS, multiples exhibit a distinct risk profile (higher ART, lower previa, fewer prior cesareans). Conclusion: Multiple gestation is not an independent risk factor for placenta previa. The observed association is driven by ART and obstetric history. Future population-based studies must adjust for mode of conception, prior cesarean details, parity, and chorionicity.